Penerapan ISO 31000:2018 untuk Manajemen Risiko E-Ticketing Taman Rekreasi XYZ - William Frederick Worotikan; Evi Maria (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This research aims to carry out a risk management process for the e-Ticketing application at XYZ Recreation Park using ISO 310000:2018. The stages in risk management start from the process of communication and consultation, setting the context, and risk assessment, which includes the steps of identification, analysis, and evaluation of risk and the risk treatment process. The research results found that there were 33 potential risks arising from the implementation of the e-Ticketing application at XYZ Recreation Park. Of the 33 potential risks, there are four potential risks at a high level: the loss of network connection, incorrect customer data, the customer requesting a refund, and the system cannot verify transactions. Seventeen are potential risks at the medium level, and the remaining 12 are possible at the low level. The XYZ Recreation Park management has proposed these potential risks for handling. The results of risk management on the e-Ticketing application at XYZ Recreation Park from this research have been documented to serve as a guideline for managers managing the risk of implementing e-Ticketing applications there